Digital Collaboration in Distributed Teams: Innovation, Productivity, and Global Perspectives - Hermansyah, Sam; Faradillah, Nurul (Novatio : Journal of Management Technology and Innovation, 2025)
The shift to remote work following the COVID-19 pandemic has accelerated reliance on digital collaboration tools, fundamentally transforming organizational practices. This study conducts a narrative review to examine how such tools support productivity, communication, and innovation within distributed teams. Literature was systematically gathered from Scopus, Web of Science, and Google Scholar, using targeted keywords and inclusion criteria to capture peer-reviewed research from the past five years. The synthesis integrates quantitative and qualitative evidence across sectors and regions, emphasizing both technological and human dimensions of remote collaboration. Results indicate that platforms such as Microsoft Teams, Slack, and Zoom enhance efficiency and foster innovation, with studies reporting measurable productivity gains in teams adopting these tools. Emotional intelligence and transformational leadership emerge as critical in sustaining team cohesion and mitigating stress in virtual environments. Global comparisons reveal disparities, with advanced economies benefiting from stronger infrastructure and supportive policies, while developing countries face heightened challenges due to limited access and cultural constraints. Discussion highlights systemic factors, including policy frameworks, organizational culture, and digital infrastructure, as determinants of success. The review concludes by recommending policy support for infrastructure development, continuous digital training, and leadership practices grounded in emotional intelligence. These strategies are essential to addressing current limitations and ensuring sustainable remote collaboration. The study identifies opportunities for future research on cross-cultural dynamics, long-term outcomes, and organizational-level innovation.